Cultural Aging : Life Course, Lifestyle, and Senior Worlds. - Katz, Stephen (University of Toronto Press, 2005)
""With this collection of imaginative, wide-ranging essays, Stephen Katz secures his place as his generation's foremost proponent of cultural aging.""--W. Andrew Achenbaum, University of Houston.